ANALISIS EFISIENSI USAHATANI PADI LAHAN PASANG SURUT DI DESA TELANG KARYA KECAMATAN MUARA TELANG KABUPATEN BANYUASIN - Gultom, Nurlaili Fitri; Wahyuni, Reshi (AGRIPITA JOURNAL, 2018)
As the main source of income for farmers in Telang Karyamaka Village is needed proper rice farming management in order to increase farmer production and income. To achieve this goal, farmers as a manager must be able to utilize the existing production factors optimally. This study aims to: 1) Calculate the cost production and income of tidal paddy rice farming 2). Analyze the factors of production affecting tidal paddy farming 3). Analyzing the efficient use of production factors in tidal paddy rice farming. This research was conducted in Telang Karya Village Muara Telang Sub District The method used in this research is survey method and sampling in this research is Simple Random sampling method. The results showed that income earned on rice farming in Telang Karya Village was Rp.42.954.291 per planted area per planting season. Factors that have significant effect on rice farming are: seeds, SP36 fertilizer, pesticide and labor while fertilizer variable urea and NPK fertilizers have no significant effect on rice farming. The use of inefficient production factors is urea fertilizer, NPK fertilizer and SP36 fertilizer. While the inefficient production factors are seeds, pesticides and labor.